The first uniportal VATS sleeve lobectomy in Türkiye: A case report (Annals of Medical Research, 2024)
In recent years, video-assisted thoracic surgery (VATS) has become the gold standard approach in the surgical treatment of early-stage non-small cell lung cancer. Especially in cases of central tumors, sleeve lobectomies that preserve parenchyma and respiratory reserves are performed instead of pneumonectomies by experienced clinics. Here, we present the first case of uniportal VATS right bronchial sleeve upper lobectomy for right main bronchial invasion in Turkey, which was successfully performed in August 2022.  A patient diagnosed with laryngeal carcinoma who had been in remission for 5 years complained of a cough. Computed thoracic tomography showed hilar peribronchial thickening and an endobronchial lesion (EBL) extending from the right upper lobe bronchus to the main bronchus, almost completely obstructing the upper lobe bronchus. Bronchoscopy revealed that the right upper lobe entrance was obstructed with EBL, and its distance to the carina was 1.6 cm. Bronchoscopic biopsy revealed squamous cell carcinoma.The thorax was entered through an incision of approximately 3 cm in the right fifth intercostal space. First, the right upper lobe pulmonary arteries and superior pulmonary vein were dissected and cut. The main bronchus was divided until the intermediate bronchus. With the help of an endoscissor, the main and intermediate bronchus were incised with appropriate surgical margins, and the lobectomy material was removed. Both macroscopic appearance and frozen and microscopic main and intermediate bronchus surgical margin tumor negativity were confirmed. One suture was passed through the lateral cartilage from the inside out, and the needle was fixed to the posterior pleura. Membranous and cartilage parts were continuously anastomosed with a double-needle 3/0 prolene suture at 2–3 mm intervals. Pathological evaluation confirmed squamous cell carcinoma with a tumor diameter of 1.7 cm, hilar 1/11 lymph node metastasis, and negative surgical margin.Adhering to oncologic principles, sleeve resections, which are difficult even with the currently known open techniques, can be performed effectively and safely with uniportal VATS in experienced centers.
Keywords: Uniportal VATS; Sleeve lobectomy; Anastomosis; Lung cancer